Mobile collocated interactions with wearables: past, present, and future - Lucero, Andrés; Clawson, James; Fischer, Joel E.; Robinson, Simon (Springer Verlag, 2016)
This Special Issue focuses on the emerging use of wearable technologies for mobile collocated interactions. Rather than merely listing off the articles that follow, we wish to introduce this Special Issue by discussing the past, present, and future of this field in HCI through its theories, ongoing designs and research efforts, and emerging frame- works. We conclude by providing an overview of a series of workshops on the topic, and introduce the two main articles that comprise this Special Issue.